2019
DOI: 10.5430/ijfr.v10n5p387
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Paper on SERVQUAL-Framework for Assessing Quality of Internet of Things (IoT) Services

Abstract: Service quality possesses the vital prominence in usability of innovative products and services. As Technological innovation has made the life synchronized and effective, Internet of Things (IoT) is matter of discussion everywhere. From users' perspective, IoT services are always embraced by various system characteristics of security and performance. A service quality model can better present the preference of such technology customers. The study intends to project theoretical model of service quality for Inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 70 publications
(92 reference statements)
0
13
0
1
Order By: Relevance
“…Tujuan dari penggunaan dimensi Servqual dalam pengukuran kesenjangan adalah untuk melakukan program perbaikan dalam pengendalian jasa layanan yang digunakan sebagai alternatif usulan dalam perbaikan kualitas jasa yang berorientasi terhadap kepuasan pelanggan, sebagai salah satu strategi perusahaan dalam memberdayakan Total Quality Service. Kualitas layanan dibangun dari semua fungsi sumber daya yang digunakan dalam berusaha (Hizam & Ahmed, 2019). Hasil pengolahan data kuestioner akan dilakukan dengan menggunakan analisa diagram Kartesius dan probabilistik kesenjangan (gap), yang merupakan penerapan dari Metode Servqual (Service Quality) Perbedaan data harapan dan persepsi dapat ditunjukkan dalam analisa statistik (Vencataya et al, 2019).…”
Section: Metodeunclassified
“…Tujuan dari penggunaan dimensi Servqual dalam pengukuran kesenjangan adalah untuk melakukan program perbaikan dalam pengendalian jasa layanan yang digunakan sebagai alternatif usulan dalam perbaikan kualitas jasa yang berorientasi terhadap kepuasan pelanggan, sebagai salah satu strategi perusahaan dalam memberdayakan Total Quality Service. Kualitas layanan dibangun dari semua fungsi sumber daya yang digunakan dalam berusaha (Hizam & Ahmed, 2019). Hasil pengolahan data kuestioner akan dilakukan dengan menggunakan analisa diagram Kartesius dan probabilistik kesenjangan (gap), yang merupakan penerapan dari Metode Servqual (Service Quality) Perbedaan data harapan dan persepsi dapat ditunjukkan dalam analisa statistik (Vencataya et al, 2019).…”
Section: Metodeunclassified
“…Then based on the quality of service interaction, 16.2% strongly agreed, 65.1% agreed, 17.2% disagreed and 1.5% strongly disagreed. Furthermore, the dimensions of the quality of the user interface are 13…”
Section: Discussionmentioning
confidence: 99%
“…students arranged that application can optimize the learning process of data structure subject [6], research that discusses determine the quality of web conferencing so that students can enhance the learning process and to know the most significant indicator in the quality of e-Learning and dimensions of usability positive influence to user satisfaction [7], research that discusses the taking perspective of users about the information quality website and 95% self-confidence level is used and the result on the dimensions of information quality (usability quality, information quality, and service interaction quality) has significant influence against to user satisfaction [8], research that discusses the identify and measure involvement of End-User Computing Satisfaction (EUCS) and WebQual 4.0 model consist of usability, information quality and services interaction dimension to user satisfaction on ABC Institution website used quantitative move toward during structural equation modeling (SEM) analysis with assenting factor analysis technique [9], research that discusses the indicated that e-learning service quality was a second-order build comprise of three factors, namely, e-learning system quality, e-learning instructor and course materials quality, and elearning managerial and support service quality [10], research that discusses the evaluate e-learning websites based on the results of the WebQual questionnaire and calculations with the meaning-performance analysis method [11], research that discusses the found that level of significance and level of performance on the e-Questionnaire website that requests to be maximized in ease of use, appearance, and enhancement on the information and communication pages that must be measured by the manager of E-Questionnaire website [12], research that discusses the established IoT-Servqual model with four dimensions (i.e., Privacy, Functionality, Efficiency, and Tangibility) of many service quality models. These dimensions are essential and disposed towards the user leaning of IoT Services [13], research that discusses the quality of the website, such as Lazada. Website that used to see what quality that website has and what the importance of that quality has and website user can be used as feedback on valuation and development of Lazada website to be more cooperative to the needs and in agreement with the prospect of website user [14], research that discusses determine customer perception of service quality and analyze customer pleasure with ShopeeNwebsite, method use is the WebQual and IPA method and IPA method is use to analyze the level of conventionality and gaps based on the level of pleasure and expectations of user [15], analyze the quality of Polri Website Learning Management System (LMS) with the aim of knowing the quality of Polri LMS website from the website user side, in this case Polri students, measured through WebQual 4.0 move toward with three main dimensions, namely Usability, Information Quality, and Service Interaction Quality [16], research that discusses determine and explain the Higher Education Services Institution Region IV website quality using the WebQual 4.0 method [17], research that d...…”
Section: Related Workmentioning
confidence: 99%
“…But knowledge management, a crucial aspect of digital competency, enables educators to facilitate any learning environment [11], [13]. Hence, further studies can focus on this particular phenomenon in the context of embracing virtual education systems and pondering over the usage enabling features such as system and service quality of VLE can also yield useful insight [36]. On the other hand, we have reconciled the digital competency construct, an individual characteristic, with the TTF model underlying a solid theoretical foundation.…”
Section: Research Limitations and Further Recommendationsmentioning
confidence: 99%